Decision-Making Process Associated with Adding NCAA Division I Sports Programs - Sloane Milstein; Zack Damon (University of Kansas Libraries, 2021)
Recent college sport headlines highlight the decision to cut teams during the COVID-19 pandemic. Citing the expected budgetary impact, Old Dominion announced it was cutting its wrestling program.  St. Edward's University is cutting the men and women's tennis, men and women's golf, and men's soccer.  The University of Cincinnati eliminated its men's soccer program with more programs to follow. Yet, a number of institutions are charging forward and have announced the addition of a team(s) to their athletic offerings.  Plymouth State will add men's swimming, Indiana Tech is adding women's ice hockey, and Augustana College just added men and women's water polo. Such additions are somewhat surprising given the difficult economic climate currently facing higher education and intercollegiate athletics. This study sought to identify a structure that NCAA Division I decision-makers took part in when adding a team in previous years.  Accordingly, the authors conducted expert-based, in-depth, semi-structured interviews with 15 Division I athletic administrators representing 23 sport teams. The following decision-making phases were identified: Identification, Justification, Evaluation, Acceptance (or Interruptions), and Authorization. Theoretical and practical implications for institutions seeking to grow their sport offerings are provided.